AKTIVASI KBBI VI DARING DALAM KAJIAN HERMENEUTIKA SCHLEIERMACHER PADA LAGU MENDARAH KARYA NADIN AMIZAH - Gulyanto, Bambang; Maulidiah, Rina Hayati; Siregar, Evi Supriyani; Daulay, Alwi Syahputra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to analyze the meaning of words by utilizing KBBI VI and language style in the lyrics of the song "Mendarah" by Nadin Amizah through a Schleiermacher hermeneutic study. This approach is used to interpret the grammatical aspects of song lyrics which are full of symbolism and figures of speech. Through this analysis, the researcher tries to understand the deep message conveyed by the author. The results of the research show that the use of word choices and figures of speech in songs is able to convey an atmosphere of sadness and hope effectively, while strengthening the symbolic meaning contained therein. Schleiermacher's hermeneutical study of this song not only functions as a work of art, but also becomes a medium for expressing the depth of feelings and longing for a father figure who is physically and emotionally distant. This analysis is able to reveal deeper layers of meaning from the song's lyrics. Overall, this research shows that musical works of art can convey emotional messages effectively through the use of figures of speech, thereby building a strong emotional connection between the work and its listeners. Keyword: Hermeneutic Studies, Schleiermacher, figure of speech, Mendarah Song Abstrak: Penelitian ini bertujuan untuk menganalisis makna kata dengan memanfaatkan KBBI VI dan gaya bahasa dalam lirik lagu "Mendarah" karya Nadin Amizah melalui kajian hermeneutika Schleiermacher. Pendekatan ini digunakan untuk memaknai aspek gramatikal dari lirik lagu yang sarat akan simbolisme dan majas. Melalui analisis ini, peneliti berusaha memahami pesan mendalam yang disampaikan pengarang. Hasil penelitian menunjukkan bahwa penggunaan pilihan kata dan majas dalam lagu mampu menyampaikan suasana sedih dan harapan secara efektif, sekaligus memperkuat makna simbolik yang terkandung di dalamnya. Kajian hermeneutika Schleiermacher pada lagu ini tidak hanya berfungsi sebagai karya seni, tetapi juga menjadi media ekspresi kedalaman menyampaikan perasaan dan kerinduan terhadap sosok ayah yang jauh secara fisik maupun emosional. Analisis ini mampu mengungkap lapisan makna yang lebih dalam dari lirik lagu tersebut. Secara keseluruhan, penelitian ini menunjukkan bahwa karya seni musik dapat menyampaikan pesan emosional secara efektif melalui penggunaan majas, sehingga mampu membangun koneksi emosional yang kuat antara karya dan pendengarnya. Kata kunci: Kajian Hermeneutika, Schleiermacher, Majas, Lagu Mendarah.